EFEK PERTUMBUHAN PLANLET PISANG RAJA (Musa paradisiaca) DENGAN PEMBERIAN BERBAGAI MACAM DAN KONSENTRASI MINYAK ATSIRI - Ulhusna, Agusti Pratama; Darini, Maria Theresia; Kusdiarti, Lilik (JURNAL ILMIAH AGROUST, 2017)
This research aim to know the effect of essential oil and its concentrations on the growth of banana plantlets. The experiment has been done in tissue culture laboratory of banana germplasm unit in Yogyakarta Spesial Territory (DIY). This study has been done in September until November 2016. It was a 3 x 3 factorial experiment and one control, arranged in a completely randomized design (CRD) with three replicates. The treatment consists two factors. The first factor is essential oil consisting of three kinds of essential oil i. e. clove oil, gandapura oil, and red ginger oil. The second factor is the concentration of essential oil which is 500, 750, and 1,000 ppm. Each treatment consisted of three bottles. The explant were obtained from 6 months old subculture. Variables observed were changes in plantlets height, fresh weight and dry weight of plantlets, root number of plantlets, and number of new growing plantlets. The results showed there’s no interaction between kinds and concentration of essential oil on the growth of banana plantain plantlets. The effect of red ginger oil on plantlets growth is better than clove and gandapura oil. Red ginger oil cause new plantlets grow faster and the concentration of 500 ppm yield the highest number of new growing plantlets.